The Relationship Between Pulse Pressure and Hypervolemia in Hemodialysis Patients - EVİRGEN, Sami; YILDIZ, Alaattin (Bulent Evcevit University, 2021)
Aim: Hypervolemia is a common problem in hemodialysis (HD) patients. Because reaching to optimal dry weight (DW) is difficult. Chronic volume overload causes left ventricular hypertrophy. Therefore, risk of cardiovascular events is very high. High pulse pressure is an indicator of aortic stiffness, an independent risk factor for cardiovascular mortality. Pulse pressure has a strong correlation with systolic blood pressure and thus with myocardial infarction in hypertensive HD patients. Aim of this study is to investigate the relationship between pulse pressure (PP) and hypervolemia. Material and Methods: Seventy (28 male (40%), 42 (60%) female) chronic HD patients with an average of age 48 ± 12 were enrolled. All patients underwent HD 3 times weekly were included. Fluid status [Total Body Water (TBW), ECW and Intracellular Water (ICW) values] was assessed twice (beginning and end of the HD) in HD patients with the body composition monitor (BCM). And blood pressure was measured simultaneously. Before and after hemodialysis, the weight of the patients was measured and recorded. Results: At the beginning of HD, Extracellular Water (ECW) / body weight (BW) (%) was associated systolic blood pressure (SBP) and PP measured simultaneously (P=0.021, P=0.057 respectively). There was no association between diastolic blood pressure with hypervolemia and PP. Conclusion: If patients have hypervolemia especially in the interdialitic period, they have prolonged exposition to cardiovascular risk factors, because hypervolemia is corralated with SBP and PP as well. Both of them are strongly associated with cardiovascular events. Removal of adequate fluid to obtain optimal dry weight causes decrease of systolic and pulse pressure proportionally.
Keywords: 3. Good health